Evaluation of the Family Hope Program (PKH) in Krembangan Utara, Pabean Cantian District, Surabaya - Indah Ramadhani; Tjitjik Rahaju; Indah Prabawati; Ahmad Niar Hilmi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to describe the evaluation of PKH in Krembangan Utara Village, Surabaya City. This research used a qualitative approach with a descriptive research type. Research subjects were determined using purposive sampling and snowball sampling techniques. The research focus employed William N. Dunn’s public policy evaluation theory, consisting of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. Data collection techniques included observation, interviews, and documentation. The data analysis techniques used were data collection, data reduction, data presentation, and conclusion drawing. The results showed that PKH in Krembangan Utara Village still faces several obstacles in its implementation. In terms of effectiveness, the objectives of PKH have generally been achieved, although the benefits have not been fully felt by all beneficiary families. In terms of efficiency, facilitators still face task limitations and insufficient operational funds. The adequacy indicator has not shown optimal results because assistance remains limited in meeting all the basic needs of beneficiary families. Equity has also not been implemented properly, as there are still beneficiaries who do not match the criteria stipulated in the regulations. Responsiveness is considered very good due to the existence of complaint mechanisms and direct assistance. In terms of accuracy, PKH has not fully addressed the problems faced by poor families because the program benefits have not been fully experienced by all beneficiary families.